Praxeologias da educação estatística na formação de professores dos anos iniciais : o caso do pensamento transnumerativo - Maranhão, Wilson Monteiro de Albuquerque (2021)
ABSTRACT: In all societies and generations, data has always been generated and information has also been passed on at all times, but never in human history have people had such broad and immediate access to this data and information. In certain situations, they are intentionally distorted, generating informational disorders for the entire community. These are the times we live in, where there is an urgent need for citizens to be prepared to question the knowledge that comes to them. For these times, two theories are very suitable for Statistics and the Anthropological Theory of Didactics (ATD): Statistics with its constructs allows the individual to receive, work and draw conclusions about the data that are available to them and ATD with its vision of a new educational paradigm, the paradigm of questioning the world, is opposed to the current paradigm, the monumentalist paradigm. In the pedagogy of questioning the world, the subject is encouraged to exercise his citizenship by investigating phenomena of any nature (social, physical etc.), and statistical tools enable the treatment of the answers obtained. However, this capacity for questioning and analysis is not acquired overnight, a statistical culture and questioning of the world must be built. The present study, of qualitative methodology, aims to: Analyze the contributions of praxeologies that favor the development of transnumerative thinking in the praxeological equipment of undergraduates in the Licentiate Degree in Pedagogy. And answer the question: What praxeologies can favor the development of transnumerative thinking with undergraduates of the Licentiate Degree in Pedagogy from a Study and Research Path? For this, a Study and Research Pathway (SRP) was carried out to train teachers in the early years of elementary school, aimed at praxeologies that enable the development of transnumerative thinking. As its founder, Yves Chevallard, points out, every SRP is composed of conditions and restrictions that must be managed during its course, so the COVID-19 pandemic and a power outage in the state of Amapá proved to be restrictions on the SRP carried out, and the conditions imposed by them were administered, such as, for example, the use of a remote learning platform to carry out the sessions. During this research, two paths were revealed, one related to research and the other related to practice, the first with characteristics of a Study and Research Pathway for Teacher Education. The completion of the study and research path of practice provided confirmation of the thesis: A Study and Research Pathway (SRP) applied in the Licentiate Degree in Pedagogy will trigger praxeologies favorable to the development of transnumerative thinking. It is believed that this study has great potential to contribute to education and other research that seek the development and sophistication of statistical literacy in our society, thus allowing the formation of citizens increasingly aware of the reality that surrounds them.